FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SAFE BEHAVIOR PADA PEKERJA REKANAN BAGIAN SIPIL DI PT. INDONESIA POWER UP SEMARANG - R. Achmad Zaindy Fara; Bina Kurniawan; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Safe behavior is a systematic application of psychological research on human behavior on safety issues in the workplace. Worker’s responses to safety are seen in their daily behavior with work conducting ethic in the workplace. Indonesia Power UP Semarang Company is one of the companies that implements safe behavior on every worker, both internal and external who work in the company area. The purpose of this study was to analyze the correlation factors with safe behavior on a civil section of partners in Indonesia Power UP Semarang Company. This type of research is cross sectional study with observational study and descriptive analytic. Population of the research were the civil partners employment of the construction work of the warehouse relocation of New Block 3 PLTGU totaling 37 people. The sample in this study was drawn from total population. Worker's safe behavior was measured subjectively by using questionnaire. Rank Spearman correlation test was used as its statistical analysis. The results showed there were correlation between safe behavior with knowledge of occupational safety and health (sig=0,014), awareness of occupational safety and health (sig=0,004), perceptions of risk (sig=0,007), and motivation to behave safely (sig=0,029). There were no correlation between safe behavior with safety needs (sig=0,705) and positive reinforcement (sig=0,912). Companies should activate safety briefings every morning before work to convey workplace safety information, particularly regarding safe behavior and reward workers who prioritize safe behaviors in work.